Biorefinery Product and Energy Potential of Araucária angustifolia bark (BERTOL.) O. Kuntze - Peres, Christiano B. [UNESP]; Maia, Amanda A. D. [UNESP]; Guandique, Manuel E. G. [UNESP]; Resende, Pedro R.; Morais, Leandro C. [UNESP] (Allerton Press, 2022)
Abstract: The objective of this study was to characterize the tree bark of Araucaria angustifolia, for estimate the energy potential of this biomass as a source of renewable energy and products from biorefineries. Studies have been carried out using thermal analysis (TGA-DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and dispersive energy spectroscopy (EDS) for thermochemical and morphological analysis. Through thermal analysis, it is possible to observe in A. angustifolia the thermal effects in the presence of air and nitrogen for a dry sample and its phases in view of the effects of temperature and mass loss. A calorific value measured around 12.23MJ/Kg was also seen, being able to consider this product as an alternative energy source and products such as maltol were identified indicating that substances from biorefineries are present in this biomass.
Keywords: bark biomass; Bioenergy; biorefineries products